Prevention care for secondary health conditions among people living with spinal cord injuries: research protocol - Pilusa, S.; Myezwa, Hellen; Potterton, Joanne (Springer Nature, 2019)
Objective: People living with spinal cord injuries are at a high risk to experience preventable secondary health conditions in their lifetime, which can lead to rehospitalisation and death. Given the fact that spinal cord injury is a long term disability requiring on-going care, there is need to strengthen prevention of secondary health conditions. This study aims to establish factors influencing prevention care for secondary health conditions among people living with spinal cord injuries in a metropolitan area in order to develop a prevention model of care. Results: A record review of patients living with spinal cord injuries will be conducted to identify the prevalence of secondary health conditions and associated factors. Semi-structured interviews will be conducted on patients living with spinal cord injuries, their caregivers and therapists to explore the contextual factors (personal and environmental factors) influencing the prevention of secondary health conditions. Thematic analysis will be used to identify the themes. Nominal group technique will be used to develop the prevention model of care for secondary health conditions. This study will be conducted at a tertiary and specialised rehabilitation hospital in South Africa.
Keywords: Injuries; Spinal cord; Spinal cord trauma; Preventative care; Prevention intervention; Secondary complications; Secondary conditions; SDG-3: Good health and well-being